PB2 and PA mutations contribute to the pathogenicity of mouse-adapted pdmH1N1-Venus reporter influenza A virus in a mammalian model - Wu, Shixiang; Yi, Ruonan; Tao, Yingying; Wu, Huimin; Wu, Li; Song, Jiasheng; Zhang, Xin; Yang, Beibei; Wu, Xing; He, Yulong; Shu, Jianhong; Feng, Huapeng (Frontiers in Microbiology, 2025)
Influenza A viruses have been a threat to human health for the past 100 years. Understanding the dynamics and pathogenicity of the influenza viruses in vivo is of great value in controlling the influenza pandemic. Fluorescent protein-carrying recombinant influenza virus is a substantially useful tool for studying viral characteristics in vivo and high-throughput screening in vitro. In this study, we generated a recombinant pdmH1N1 CA04 influenza virus carrying a Venus reporter gene in the non-structural (NS) segment using reverse genetics. After passaging the recombinant influenza virus carrying Venus from lung to lung in mice, we found that virulence of the passaged pdmH1N1 CA04-Venus significantly increased and was lethal to the mice. We finally isolated one mouse-adapted pdmH1N1 CA04-Venus with bigger plaques expressing the amount of Venus proteins by using the ninth passage lung homogenate with plague purification. We found three different amino acids (PB2 T340K, PA I21M, and F175L) between WT-CA04-Venus and MA-CA04-Venus using whole-genome sequencing. Interestingly, the polymerase activity of MA-CA04-Venus was significantly lower than that of WT-CA04-Venus in a minigenome assay. Further investigation demonstrates that PA I21M and PA I21M + PB2 T340K significantly enhanced the polymerase activity of WT-CA04-Venus; however, PA F175L + PB2 T340K significantly decreased the polymerase activity of MA-CA04-Venus. Therefore, PA I21M mutation may determine the increased virulence in mice, and PA F175L + PB2 T340K may be involved in the stability of Venus insertion. Above all, we generated a mouse-adapted pdmH1N1 CA04-Venus virus with high virulence and stable green fluorescent Venus protein. It is a useful tool for high-throughput screening of antiviral drugs and for investigating the interaction between the influenza virus and host in vivo.